Tuloy ang biyahe examining the lived experiences of pedicab driver-beneficiaries in Pavia, Iloilo - Espere, Roselle Angela B.
Pedicab drivers are among the hardest-hit sectors of the COVID-19 pandemic as their livelihood has been impeded due to mobility restrictions resulting in decreased income. This has also affected the lives of their families as less income has limited their ability to satisfy their daily needs. As a response to this situation, the Ayala Foundation, Inc. launched the Tuloy Ang Biyahe Project to provide financial assistance through an interest free loan and grant to be utilized as capital for a micro enterprise. Through in depth and key informant interviews, the study examined the lived experiences of 10 pedicab drivers in Balabag, Pavia, Iloilo as transport service providers, TAB beneficiaries, and micro entrepreneurs. Data was analyzed using Colaizzi's Descriptive Phenomenological Method. The results of the study showed that pedicab drivers were greatly affected by the COVID-19 pandemic which led them to develop coping strategies to sustain their family's needs. Moreover, it was found out that the TAB project was a significant help in coping with the effects of the pandemic due to increased income from the alternative source of livelihood supported by TAB. The pedicab drivers also exhibited certain skills and attitudes that enabled them to cope with their struggles and led to their success in sustaining their micro enterprise. Factors that may have contributed to the success include proper project orientation, monitoring, their positive attitude and sense of industry and the assistance provided by the women members of the family serving as microenterprise managers. Nevertheless, there is a need to further support the sector to ensure their full recuperation from the COVID 19 pandemic as well as to strengthen their potential as micro-entrepreneurs.